علم الجمال بين الفلسفة اليونانية والفلسفة الإسلامية: دراسة تحليلية مقارنة: Aesthetics between Greek and Islamic Philosophy: A comparative analytical study - Alshashaa, Areej Ali; AlHarthi, Abdulrahman Mohammad N (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث يعالج البحث نظرية فلسفية شغلت حيزاً كبيراً في كتابات فلاسفة اليونان، وفلاسفة الإسلام ألا وهي علم الجمال، ويهدف البحث إلى تتبع علم الجمال في الفلسفة اليونانية والإسلامية، مع بيان أوجه الاتفاق والاختلاف، ومواطن التأثير والتأثر، وبيان مدى تأثير المادية على فكر وكتابات فلاسفة اليونان، مع عمل موازنة ومقارنة حول علم الجمال في الفلسفة اليونانية والفلسفة الإسلامية، واستخدم الباحثان المنهج الوصفي التحليلي، والمنهج النقدي، والمنهج المقارن، وتوصل البحث إلى أن علم الجمال في الإسلام شمولي يشمل حياة الإنسان الدينية والدنيوية، وكذلك تبين من خلال طرح علم الجمال بين الفلسفة اليونانية والفلسفة الإسلامية وجود أوجه اتفاق وتوافق، وتأثير وتأثر ببعض المنطلقات الفكرية، وأوجه اختلاف وتباين فيما يتعلق بالتوجهات الدينية والروحية، وتوصل البحث أيضاً إلى أن علم الجمال في الفلسفة اليونانية مادي بينما في الفلسفة الإسلامية مادي وروحي في نسق فلسفي إسلامي، ويوصي البحث بإجراء دراسات مماثلة في قضايا فلسفية أخرى دراسة تحليلية مقارنة، وبيان موقف الإسلام منها Abstract The research deals with a philosophical theory that occupied a large space in the writings of Greek philosophers, and philosophers of Islam, namely aesthetics, and the research aims to track aesthetics in Greek and Islamic philosophy, with a statement of aspects of agreement and difference, and areas of influence and influence, and a statement of the extent of the impact of materialism on the thought and writings of Greek philosophers, with a balance and comparison work on aesthetics in Greek philosophy and Islamic philosophy, and the researchers used the descriptive analytical approach, the critical approach, and the comparative method, and the research found that aesthetics in Islam is holistic Human religious and worldly life, as well as showing through the introduction of aesthetics between Greek philosophy and Islamic philosophy the existence of aspects of agreement and compatibility, and the impact and influenced by some intellectual premises, and differences and differences with regard to religious and spiritual orientations, and the research also found that aesthetics in Greek philosophy is material while in Islamic philosophy material and spiritual in an Islamic philosophical system, and the research recommends conducting similar studies in other philosophical issues comparative analytical study, and a statement of Islam’s position thereof.